PROBLEMS WITH REDUCING THE AMOUNT OF PENALTY (NEUSTOYKA) BY THE COURT (TSUL LEGAL REPORT, 2026)
Ensuring the fulfillment of contractual obligations is now of paramount importance. Therefore, it is more important than ever to do research on this issue. This article discusses ways to secure an obligation. in particular, the concept of neustoyka, in which the views of scientists are presented. forms of penalty (neustoyka) and its legal nature are discussed. It also considers the theoretical and practical aspects of the problem of reducing the amount of fines, which is currently the subject of heated debate in the Republic of Uzbekistan (Article 326 of Civil Code of the Republic of Uzbekistan), gives examples from court practice and compares with foreign experience. Reducing the amount of penalty (neustoyka) by the courts suggests the prevention of possible corruption cases and a reasonable solution to the problem. including proposals for the revision of Article 326 of Civil Code of the Republic of Uzbekistan, which shall be stated by reasoned opinions. Moreover, aspects that can be drawn from foreign experience are discussed.